The Stock Potency of Demersal Fish Resource at The Coastal Zone, East Kutai District in East Kalimantan - Juliani Juliani; Iwan Suyatna (Chemical Engineering Diponegoro University, 2014)
The objective of this research was to estimate the potency of demersal fish resource spread over three sub-districts i.e. Sangkulirang, Sandaran and Kaliorang in Kutai district, East Kalimantan province. The result showed that the highest total biomass was produced by aquatic zone of Sandaran sub-district with 1,763,713.6 ton/zone and the density stock was 13,566.5 kg/km2. It was followed by Sangkulirang sub-district with 264,653.3 ton/zone and 6,640.4 kg/km2, respectively and then by Kaliorang sub-district with 58.086,5 ton/zone and 2,768.0 kg/km2, respectively. In term of species particularly from crustaseaae family, the most economic aquatic zone was found in Sangkulirang sub-district. The export product species Penaeus sp was obtained from Penaeus monodon, Metapenaeus monoceros, Metapenaeus sp, Parapenaeopsis sculptilis, Penaeus sp, and lobster which was accounted by 3,381.6 tons/zone, 83,199 tons/zone, 14,492.7 tons/zone, 24,691.3 tons/zone, 41,331.1 tons/zone, and 1,073.5 tons/zone, respectively. It was followed by Sandaran sub-district with export product species was Penaeus merguensis 33,495.7 tons/zone and non-export products were Parapenaeopsis sculptilis 63,641.7 tons/zone, Penaeus sp 16,747.8 tons/zone, Metapenaeus sp 1.674,8 tons/zone, Caridina sp 1.562.572,2 tons/zone, and Scylla serrata 3,349.6 tons/zone. Next was Kaliorang sub-district which accounted by Penaeus merguensis 62.2 tons/zone and Metapenaeus monoceros 49.7 tons/zone. In situ measurement on seven physical-chemical quality parameters of water which compared to the standardized of sea water showed that water quality found in coastal zone of Kaliorang, Sangkulirang and Sandaran sub-district, East Kutai province was suitable and feasible for the aquatic and living of marine habitats